2020
DOI: 10.1177/1558925019899680
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melt spinning parameters on polypropylene hollow fiber formation

Abstract: The objective of this research was to explore the effects of processing conditions on hollow fiber spinning, specifically to look at how differences in solidification impact hollow and solid fiber structures. Polypropylene hollow fibers were melt-spun with a four-segmented arc (4C) die under the wide ranges of spinning conditions (0.25–0.83 g/min of polymer mass throughput per a fiber, 500–2000 m/min of spinning speed, and 5%–100% quench rate). Fiber structure was explored through thermal, geometric, and tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although PP exhibits comparatively low hydrophobicity, previous investigations have indicated that PP exhibits the best performance in MD due to its physical-chemical stability and easy processing [25][26][27][28]. Polypropylene (PP) is a semicrystalline polymer with a surface energy reaching 30.0 × 10 3 N/m, which provides enough hydrophobicity for the microporous membrane applied to the MD process [29][30][31]. Considering sufficient handling capacity as well as the limits on the dimensions and mass for space applications, a homogeneous PP hollow fiber membrane with a high surface area to volume ratio was fabricated by melt-spinning and stretching in this study.…”
Section: Membrane Fabrication and Characteristicsmentioning
confidence: 99%
“…Although PP exhibits comparatively low hydrophobicity, previous investigations have indicated that PP exhibits the best performance in MD due to its physical-chemical stability and easy processing [25][26][27][28]. Polypropylene (PP) is a semicrystalline polymer with a surface energy reaching 30.0 × 10 3 N/m, which provides enough hydrophobicity for the microporous membrane applied to the MD process [29][30][31]. Considering sufficient handling capacity as well as the limits on the dimensions and mass for space applications, a homogeneous PP hollow fiber membrane with a high surface area to volume ratio was fabricated by melt-spinning and stretching in this study.…”
Section: Membrane Fabrication and Characteristicsmentioning
confidence: 99%
“…The extrusion rate is limited by the flow instability and high viscosity of spinning liquids and melt dopes. Therefore, achieving a high draw ratio is the main approach for attaining fast spinning and is an important technique for industrial fiber production with spinning speeds above 100 m min –1 . Graphene fiber (GF) is a new type of carbonaceous fiber that exhibits excellent functionality when compared with traditional carbon fibers based on polyacrylonitrile (PAN) and mesophase pitch. Optimization over the past decade has led to GF with electrical and thermal conductivities of 1.19 × 10 6 S m –1 and 1480 W m –1 K –1 , respectively . However, the spinning speed of GF is still low, which hinders wider GF research and realistic application.…”
mentioning
confidence: 99%